Assessing concordance between Campylobacter prevalence in broilers and human cases before and during the COVID-19 pandemic in Lower Saxony, Germany, considering fresh chicken meat consumption patterns - Nolte, Tobias; Spieß, Fabian; Jacobs, Anne-Katrin; Kemper, Nicole; Visscher, Christian (Frontiers in Veterinary Science, 2024)
As the most common foodborne disease, number of campylobacteriosis decreased in Germany with the beginning of the COVID-19 pandemic in 2020. As the consumption of fresh chicken meat is a major risk factor for human infection, this study investigated the relationship between Campylobacter contamination levels on chicken carcasses and human cases in Lower Saxony, Germany and observed fresh chicken meat consumption patterns between 2018 and 2021 including the time of the COVID-19 pandemic. Campylobacter levels in broilers and human cases were classified based on the median and descriptively analysed per week using contingency tables. Before the COVID-19 pandemic (2018COVID-19 pandemic ( & 2019)), high Campylobacter contamination levels on neck samples and many human cases were more present, whereas with the beginning of the COVID-19 pandemic (2020 & 2021), low contamination levels on chicken carcasses and few human cases were more present. Lowest concordance between both parameters was shown in 2018 (Cohen's cappa coefficent: 0.37) and 2020 (0.38). The highest concordance was examined in 2021 (0.69). The McNemar test indicates that other risk factors for campylobacteriosis not related to meat quality (such as travelling abroad and eating at restaurants) were less relevant during the period of the COVID-19 pandemic compared to previous years. The private consumption of fresh chicken meat in Lower Saxony increased significantly with the beginning of the COVID-19 pandemic in 2020 by 63.9 tonnes compared to 2019 to an average of 453.5 tonnes per week. Public health measures and a reduced number of medical treatments have undoubtedly had an impact on less reported human cases during the COVID-19 pandemic. However, number of human cases in 2023remained in 2023 at a low level in Germany in 2023 while chicken meat consumption increased. Thus, further risk assessments regarding the risk of campyloabcteriosis due to chicken meat consumption should include the country of origin, as the level of contamination of chicken carcasses varies between European countrieswith Formatiert: Schriftart: Kursiv around 40,000 human cases in 2023, the number of campylobacteriosis have remained at a low level in Germany since the COVID-19 pandemic.